The association between helicopter emergency medical services and early casualty survival: a nationwide study. (28th July 2022) - Guinzburg, Ariel; Gelikas, Shaul; Tsur, Avishai M.; Nadler, Roy; Sorkin, Alex; Avital, Guy; Radomislensky, Irina; Bodas, Moran; Segal, David; Benov, Avi; Chen, Jacob
Abstract : Background: Helicopter emergency medical services (HEMS) allow for shorter transport duration in long-distance evacuations and facilitate advanced en-route medical care access. Studies comparing HEMS with ground emergency medical services (GEMS), including the outcome of prehospital mortality, are lacking. Objective: This study aimed to evaluate the association between HEMS and early mortality in Israel. Setting: A retrospective cohort study was conducted of the cross-referenced Israel Defense Forces Trauma Registry and Israel National Trauma Registry databases. Outcome measures and analysis: Univariable logistic regression was used to assess the association between HEMS and early mortality, defined as mortality within 1 day of the injury. Regression analysis was further performed stratifying by event type (military or civilian) or type of injury (penetrating or nonpenetrating). Results: A total of 2344 casualties were included in the study, of whom 756 (32.3%) were evacuated by air. Early mortality rates were 90/1588 (5.7%) and 37/756 (4.9%) in GEMS and HEMS groups, respectively. Regression analysis found no significant analysis between HEMS and early mortality [OR, 0.86 (95% CI, 0.57–1.26)]. Stratified by event type, a nonsignificant association between HEMS and early mortality was demonstrated for combat [OR, 1.69 (95% CI, 0.79–3.92)] and noncombat [OR, 0.73 (95% CI, 0.4–1.25)] events. HEMS was associated with decreased early mortality among casualties with a penetrating injury [OR, 0.59 (95% CI, 0.34–0.98)] but not associated with early mortality among casualties with a nonpenetrating injury [OR, 0.84 (95% CI, 0.43–1.52)]. Conclusion: HEMS was not associated with a decrease in early mortality among trauma casualties in this study encompassing the prehospital and hospital scenes. There was a positive trend and a decrease in mortality from penetrating injuries. Further research to ascertain which casualties benefit from HEMS is warranted and will allow for more precise use of this expensive resource.